The Role of Profitability in Moderating the Effect of Capital Structure, Profit Growth, Cash Flow, and Tax Planning on Financial Distress (In Transportation and Logistics Companies Listed on the Indonesia Stock Exchange for the 2021–2024 Period): Pada Perusahaan Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024 - Farras Putri Ramadhani; Hustna Sarra Dara; Imam Hidayat (JURNAL ECONOMINA, 2026)
This study aims to empirically analyze the role of profitability as a moderating variable in the effect of capital structure, profit growth, cash flow, and tax planning on financial distress in transportation and logistics sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This study employed a quantitative approach using secondary data in the form of annual financial statements obtained from the official website of the Indonesia Stock Exchange. The sample was determined using purposive sampling method, resulting in 19 companies as research objects during the observation period. The data analysis technique used was panel data regression with the Moderated Regression Analysis (MRA) approach using EViews 12 software. The results showed that capital structure and cash flow had a significant negative effect on financial distress, while profit growth and tax planning had no significant effect. Profitability was also proven to strengthen the effect of capital structure, profit growth, and cash flow on financial distress, but was unable to moderate the effect of tax planning on financial distress